Analisis Kelengkapan Form Resume Medis Pasien Rawat Inap BPJS Di RSJ Prof. HB. Saanin Padang - Nurmaines Adhyka; Ryan Pratama Putra; Indri Mayani; Sevia Etika Ambarsari; Tara Hafizah; Utari Nurul Fajri; Muthia Azzahra (Jurnal Kabar Masyarakat, 2023)
The medical resume form is a summary of all patient care and treatment that has been carried out by health workers signed by the doctor. The completeness of medical resume filling in Psychiatric hospital Prof. HB. Saanin Padang only reaches 80% from the 200 patient each month. The purpose of this study was to analyze the completeness of medical resume written by the doctor in Psychiatric hospital Prof. HB. Saanin Padang. The Data collection techniques using observation, documents and interviews. Using 200 medical resumes sample in January 2023 patients. The results showed that the highest percentage of incompleteness was found in the discrepancy between the DPJP's signature and the stamp on the patient's medical resume by 5%. Adding to this the errors in the placement of writing primary diagnoses with secondary diagnoses by 5%. The conclusion that the highest incompleteness occurs is the discrepancy between the DPJP's signature and the stamp. Suggestions from researchers are conducting socialization by preparing TOR coordination with the field of Education and Training.